Ultrasound Assisted Synthesis of Polylimonene and Organomodified-clay Nanocomposites: A Structural, Morphological and Thermal Properties - Hodhaifa Derdar; Geoffrey Robert Mitchell; Zakaria Cherifi; Mohammed Belbachir; Mohamed Benachour; Rachid Meghabar; Khaldoun Bachari; Amine Harrane (Bulletin of Chemical Reaction Engineering & Catalysis, 2020)
Polylimonene-clay nanocomposites (PLM-Mag 2, 3, 6 and 10% by weight of clay) were prepared by mixing Maghnite-CTA+ (Mag-CTA+) and polylimonene (PLM) in solution using ultrasonic irradiation. The catalyst preparation method were studied in order to determine and evaluate their structural, morphological and thermal properties. The Mag-CTA+ is an organophylic montmorillonite silicate clay prepared through a direct exchange process, using green natural clay of Maghnia (west of Algeria) called Maghnite. The Algerian clay was modified by ultrasonic-assisted method using cetyltrimethylammonuim bromide (CTAB) in which they used as green nano-reinforcing filler. Polylimonene was obtained by the polymerization of limonene, using Mag-H+ as a catalyst. The morphology of the obtained nanocomposites was studied by X-ray diffraction (XRD), scanning electronic microscopy (SEM), transmission electronic microscopy (TEM) and infrared spectroscopy (FT-IR). Thermogravimetric analysis (TGA) shows that the nanocomposites have a high degradation temperature (200−250 °C) compared with the pure polylimonene (140 °C). The analyses confirmed the chemical modification of montmorillonite layers and their uniformly dispersion in the polylimonene matrix. Exfoliated structures were obtained for low amounts of clay (2 and 3% by weight), while intercalated structures and immiscible regions were detected for high amounts of clay (6 and 10% by weight). Copyright © 2021 by Authors, Published by BCREC Group. This is an open access article under the CC BY-SA License (https://creativecommons.org/licenses/by-sa/4.0).